2022
DOI: 10.1159/000523857
|View full text |Cite
|
Sign up to set email alerts
|

Primary Squamous Cell Carcinoma of the Liver: Case Report and Review of Literature

Abstract: Primary squamous cell carcinoma (SCC) of the liver is a rare cancer type. The overall survival of this cancer is short despite treatment and prognosis are poor. To our knowledge, there are around 30 cases of primary SCC of the liver described in the literature. Primary SCC of the liver is thought to be associated with a wide variety of hepatic conditions such as hepatic cyst, hepatolithiasis, or hepatic teratoma. We present the case of a 33-year-old male patient diagnosed with primary keratinizing SCC of liver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Since 1970 till date, only 31 cases of PSCC are available in literature. In these reported cases the age group in which patients presented is not fixed as review of literature showed that the minimum age of patient presenting with PSCC is 18 years while the maximum age reported is 82 years [6] . The age of patient in this case report is 25 years and in literature only 3 patients are reported below age of 25 years, 2 were 21 years old and one was 18 years old.…”
Section: Discussionmentioning
confidence: 99%
“…Since 1970 till date, only 31 cases of PSCC are available in literature. In these reported cases the age group in which patients presented is not fixed as review of literature showed that the minimum age of patient presenting with PSCC is 18 years while the maximum age reported is 82 years [6] . The age of patient in this case report is 25 years and in literature only 3 patients are reported below age of 25 years, 2 were 21 years old and one was 18 years old.…”
Section: Discussionmentioning
confidence: 99%
“…The PET/CT manifestations of PSCCL are rounded and heterogeneous low‐density mass shadows. Additionally, the metabolism of 18F‐fluorodeoxyglucose (FDG) is increased significantly 20,22,25,26 . In some studies, 20,22,25 the maximum standardized uptake value of 18F‐FDG was 11.6–21.9 (Table 1).…”
Section: Imaging Manifestationsmentioning
confidence: 99%
“…Additionally, the metabolism of 18F‐fluorodeoxyglucose (FDG) is increased significantly 20,22,25,26 . In some studies, 20,22,25 the maximum standardized uptake value of 18F‐FDG was 11.6–21.9 (Table 1). When the tumor develops peripheral lymph node metastasis, hypermetabolic enlarged lymph nodes may appear around the hilar, portal vein, paraaortic, left common iliac space, and left supraclavicular region 12,20,22,25 .…”
Section: Imaging Manifestationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary squamous carcinoma of the liver is an extremely rare and high malignant tumor with a very poor prognosis. [1][2][3][4] To date, its pathogenesis remains unclear, and clinical recognition is difficult, relying only on pathology and immunohistochemistry to confirm the diagnosis. 1,[5][6][7] Only a few sporadic cases of primary squamous carcinoma of the liver have been reported, and their PET/CT findings have rarely been described.…”
Section: Figurementioning
confidence: 99%